Sustainable and evidence based learning and teaching approaches to the undergraduate psychology curriculum : ALTC associate fellowship final report. - Cranney, Jacquelyn (Australian Learning and Teaching Council (ALTC), 2008)
'This Fellowship project intentionally responded to two of these influences. First, internationally, there is the push toward accountability in the tertiary education sector, and this is partly being operationalised at the learning and teaching coal-face through the delineation and assessment of student learning outcomes. A primary outcome of the current project was the delineation of a set of national graduate attributes (GAs) for the four-year undergraduate degree in psychology. Second, also on the theme of accountability, there is a need for improved learning and teaching strategies that facilitate students' attainment of these learning outcomes.' - Executive Summary.